The terrestrial arthropods of Rapa Nui: A fauna dominated by non-native species - J. Judson Wynne; Francis G. Howarth; Darko D. Cotoras; Sergio Rothmann; Sergio Ríos; Carolina Valdez; Pedro Lazo Hucke; Cristian Villagra; Luis Flores-Prado (Global Ecology and Conservation)
The terrestrial arthropod fauna of Rapa Nui has been negatively impacted by human activities, including accidental and purposeful species introductions, which have led to high levels of extinction and extirpation of the native fauna. Unfortunately, the absence of a single, standardized resource documenting all Rapa Nui’s native and non-native species hinders protecting surviving native species, as well as recognizing new invasions. Here, we present a comprehensive list of terrestrial arthropod species recorded up to 2024. We compiled this list from the literature, unpublished museum records, and field sampling. We also consulted 29 taxonomic specialists, who assisted in verifying species in this checklist. A total of 539 arthropod species were cataloged including 25 endemic, 27 indigenous, 345 accidentally introduced, and 66 purposefully introduced species, and 76 species of unknown origin. Most, if not all, of the unknown records represent non-native species. Eleven endemic and 14 indigenous species have not been recorded since their original description, which suggests their extinction or extirpation. However, the lack of targeted surveys prevents verification of their persistence on the island. For non-native species, one-third (33 %) have cosmopolitan or nearly cosmopolitan distributions, while 31 % originated from the tropics. Overall, this checklist will serve as a comprehensive resource for the identification of established species and facilitate the detection of new arrivals. It will also contribute to the protection of the island’s surviving native species.